Diffusion and upscaling of municipal climate mitigation and adaptation strategies in Germany - Kristine Kern; Peter Eckersley; Wolfgang Haupt (Regional Environmental Change, 2023)
Drawing on data for the 104 largest German cities, and deeper analysis of six mid-sized cities (including forerunners, followers and latecomers in climate mitigation and adaptation), we find that the spread of local mitigation and adaptation strategies across Germany can be explained by a combination of horizontal diffusion and vertical upscaling. Specifically, while the spread of climate mitigation initiatives in the 1990s was triggered primarily by transnational municipal networks (horizontal diffusion), the development and revision of climate mitigation strategies and the emergence of climate adaptation strategies during the last decade have been driven mainly by national and subnational funding programmes (vertical upscaling). Notably, forerunner cities are less dependent on external funding than followers and latecomers, because they have more internal capacity to act. By arguing that upscaling of local climate policies from forerunners to followers and latecomers depends on interventions by national and subnational authorities, we stress that the majority of German municipalities require external support in order to develop and implement effective climate strategies.
Keywords: 320; Policy diffusion; Policy upscaling; Municipalities; Local climate mitigation; Local climate adaptation; Germany